Chemical Composition and Antibacterial Activity of the Essential Oils of Semenovia frigida and Chaerophyllum bulbosum from Iran - Taherkhani, Mahboubeh; Rustaiyan, Abdolhossein; Nahrevanian, Hossein (Asian Journal of Chemistry, 2017)
The authors retract the above article for violations of the ethical guidelines to publication. This article was published without the knowledge or consent of the author/s. As a result, the authors retract this manuscript.